Pengaruh Gaya Kognitif Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Matematika - Prayoga, Susilo Adi; sofakhiroh, ifa; Puspitaningayu, Tias; Mustika Sari, Nurul Husnah (Universitas Nusa Cendana, 2024)
Cognitive style is an important factor in the learning process that differentiates between individuals or students in thinking, remembering and behaving cognitively which can influence how individuals absorb and process information. Cognitive styles are classified into two based on psychological differences: Field-independent (FI) and Field-dependent (FD). The aim of this research is to find out how cognitive style on student’s academic performance in mathematics.The approach employed in this research is a descriptive qualitative approach which emphasizes explicit literature review. Based on the studies conducted, this research shows that bothcognitive styles, whether field-independent and field-dependent have a significant influence on the learning process and student academic performance in mathematics subjects. Therefore, the use of appropriate cognitive styles in the learning process can enhance students' mathematics learning outcomes